Finding the Lost Book of the Law: Re-reading the Story of ‘The Book of the Law’ (Deuteronomy–2 Kings) in Light of Classical Literature - Stott, Katherine (Journal for the study of the Old Testament, 2005)
This article reconsiders the much discussed story of ‘the book of the law’ in 2 Kings 22–23, along with the various other references to this lawbook in the so-called ‘Deuteronomistic History’. While there has been a tendency within modern scholarship to read 2 Kings 22–23 from an historical perspective and to assume that ‘the book of the law’ was an actual book that is to be identified in some way with the book of Deuteronomy, certain commentators prefer to understand references to ‘the book of the law’ as serving a rhetorical purpose in their narrative context. This article argues that a rhetorical understanding of these references receives additional support from comparison with classical literature, where stories about lost and found documents are widely used as a literary ploy to bolster the credibility of the texts within which they appear.